Process Implementation: Islamic Education Policy in the National Education System at SMKN 1 Kediri West Lombok - Mawardi, M; Fadli, Adi; Malik, Abdul (Tadbir : Jurnal Studi Manajemen Pendidikan, 2024)
Islamic education in the National Education System of the Republic of Indonesia has an integrated relationship, including having goals and functions that are complementary and mutually supportive. Islamic education is a major part of achieving the goals of national education. This article presents the form of Islamic education implemented in public schools as an implementation process of Islamic education policy in the implementation of the national education system. Through observations, interviews, and descriptions of books, articles and documentary data collected, the researcher tries to deeply analyse and group similar data so as to produce a clear and in-depth description of the data analysis. Some of the obstacles that occur in schools indicate patterns of education that tend to be an obstacle to Islamic Education and the National Education Goals, making education stakeholders try to optimize patterns of religious education that refer to the optimization of Islamic Education Goals in national education programs in education units. This research produces several important points to strengthen the implementation of the Islamic education process in education units and concludes the importance of Islamic education in the national education system as a form of education and human development.